The spatial distribution and paleoecology of Caribbean peatlands - Emily A. Rabel; Julie Loisel (Communications Earth & Environment)
Abstract Tropical peatlands are being lost at a rate three times greater than forests, with large and rapid impacts on carbon and water cycling, biodiversity, and human health. Despite threats from land conversion and climate change, peatlands across the tropical biome remain poorly mapped, making it difficult to develop sustainable management solutions. Superimposed on this dearth of spatial data is poor knowledge of peatlands’ net carbon balance. In this Review, we synthesize information on the paleoecology, carbon dynamics, and distribution of the peatlands of the Caribbean. Though data limitations are substantial, this work contributes to further confirm peatland occurrence and further our understanding of their functioning.